Online Recruitment: A Cognitive Perspective of Job Seekers in Nepal - Poudel, Bishwash Raj (Journal of Business and Social Sciences, 2018)
IT adoption is more than just technology deployment; it requires careful consideration of social-cognitive factors. With this premise, in this paper, the behavioral intention of job seekers to use online recruitment services in Nepalese context has been examined on the basis of five determinants: Performance expectancy, Effort expectancy, Subjective Norms, Objective Norms and Facilitating conditions. The impact of predictor on outcome variable is examined using multiple regression analysis. The unified theory of acceptance and use of technology (UTAUT) has been used as basic foundation of the study.